Interferência do óleo essencial de folhas do quimiotipo II de Lippia alba (MILL.) N.E. BROWN na atividade antimicrobiana da oxacilina sobre staphylacoccus aureus oxacilina-resistente - Rocha, Larissa Queiroz (2012)
The Lippia alba (Mill.) N. E. Brown species inhabits almost all regions of Brazil, which is plenty used in popular medicine. Studies show that between the Brazilian Northeast three chemotypes of L. alba, the chemotype II (OELaII), produces in its leaves, essential oil with the largest and broadest antimicrobial potential. The objective of this study was to evaluate the interference of the OELaII in the Oxacillin activity and its mechanism of action against Staphylococcus aureus. The antimicrobial activity was performed by determining the Minimum Inhibitory Concentration (MIC) and minimum bactericidal concentration (MBC) by broth microdilution methods of culture and spreading on the surface of agar Plate-Count, respectively. The evaluation of the OELaII interference on antimicrobial oxacillin activity and other antibiotics was performed by using methodology changed disk diffusion. The checkerboard method, calculation of Fractional Inhibitory Concentration Indices and graphing Isobologramas was used to assess the interference OELaII the antimicrobial activity oxacillin. The study of the OELaII mechanism of action on strains of S. aureus was performed by evaluating the OE antimicrobial activity in the phases of exponential growth and stationary as well as by the action of chloramphenicol on the exponential growth. The effect of OELaII, oxacillin and OELaII-OXA exposure time, on strains of S. aureus was observed by tracing curves time of death, was considered synergistic association was found that a reduction in the number of viable cells after 24-48 hours when compared to each compound alone. The results revealed that the MIC and MBC OELaII to the strains of S. aureus oxacillin resistant (ORSA) are equal or very close to those observed for susceptible strains (UR) ranging from 0.312 to 1.25 mg / ml and 1.25 to 5.0 mg / mL for the first, and 0.312 -0.625 mg / mL and 0.625 to 2.5 mg / mL for the second. Oxacillin to the values obtained were 6.25 to 200 mg / ml and 25 and 400 mg / mL and 0.390 to 3.12 for ORSA mg / mL and 0.781 to 6.25 mg / mL for the UR. The study of the evaluation of synergism using the Kirby-Bauer method and checkerboad showed that the interference exerted by the essential oil on the antimicrobial action vary with the type of antibiotic and the type of strain tested. Isobologram charts obtained by checkerboard method suggests a synergism between good and OELaII Oxacillin for all the microorganisms tested. The study of the mechanism of action on inhibition OELaII /death ORSA strains, it was found that the OELaII reduced the number of viable cells in any growth stage. The same was not observed when cell division was halted by the presence of chloramphenicol, suggesting that OE acts mainly in the exponential growth phase (intense cell division). The death curve by microbial activity and OELaII Oxacillin showed a synergistic effect for the association OELaII-OXA, with a logarithmic decrease significantly when compared to treatment done alone. Given this biological potential, this study suggests that the Lippia alba can be used as a pharmaceutical ingredient in preparations of association with antimicrobial drugs in order to diminish the toxicity and increase its spectrum. However, there is the importance of studies on the elucidation of the different molecular targets through knowledge of its mechanism of action and toxicity testing in vitro, thus providing the safety and therapeutic efficacy of this important plant species users.